Implementasi Smart Contract dalam Bisnis Digital Berdasarkan Hukum Perdata - Masrofah Masrofah; Teguh Suroso; Susilo Wardani (Legalite : Jurnal Perundang Undangan dan Hukum Pidana Islam, 2025)
This study aims to analyze the implementation of smart contracts in digital business practices and to assess their legal certainty from a civil law perspective. This research employs a normative legal research method using statutory and conceptual approaches, focusing on the Indonesian Civil Code, the Law on Electronic Information and Transactions, and the Law on Financial Sector Development and Strengthening. The findings indicate that smart contracts can be legally recognized as valid agreements provided they fulfill the essential requirements of contract validity, namely consent, legal capacity, a specific object, and a lawful cause. However, the automated and code-based nature of smart contracts poses challenges in interpreting the parties’ intent, verifying legal capacity, and determining lawful cause. Therefore, stronger regulatory frameworks and hybrid contract models are necessary to ensure legal certainty for smart contracts in Indonesia.